2014
DOI: 10.1016/j.ijdevneu.2014.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of spontaneous dense array gamma oscillatory activity and minor physical anomalies as a composite neurodevelopmental endophenotype in schizophrenia

Abstract: Composite evaluation of two developmentally linked markers i.e. MPAs and gamma spectral measures may prove useful in categorizing schizophrenia and identifying at-risk individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 53 publications
(72 reference statements)
1
13
0
Order By: Relevance
“…Deficits in resting spontaneous alpha band activity reported across the clinical course of the disease (chronic SZ, first episode psychosis, prodromal SZ, relatives of SZ probrands) ( Boutros et al, 2008 ; Goldstein et al, 2015 ; Kim et al, 2015 ) were mimicked in our EEG recordings across scalp regions following NMDA antagonist treatment. They were also seen in recent MEG recordings ( Muthukumaraswamy et al, 2015 ), and were concurrent with diffuse increments in gamma also described in some recent resting state studies of SZ ( Kam et al, 2013 ; Kocsis et al, 2013 ; Tikka et al, 2013 , 2014 , 2015 ). These parallel observations with alpha and gamma spectral frequencies contrast with the response of delta-theta and beta activities to NMDA receptor blockade as the reduction in current density with ketamine, particularly in the low frequencies, is contrary to the observation that increased local and global EEG delta/theta is one of the more consistent findings reported in unmedicated, first episode, and chronic SZ patients ( Boutros et al, 2008 ; Moran and Hong, 2011 ; Kim et al, 2015 ).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Deficits in resting spontaneous alpha band activity reported across the clinical course of the disease (chronic SZ, first episode psychosis, prodromal SZ, relatives of SZ probrands) ( Boutros et al, 2008 ; Goldstein et al, 2015 ; Kim et al, 2015 ) were mimicked in our EEG recordings across scalp regions following NMDA antagonist treatment. They were also seen in recent MEG recordings ( Muthukumaraswamy et al, 2015 ), and were concurrent with diffuse increments in gamma also described in some recent resting state studies of SZ ( Kam et al, 2013 ; Kocsis et al, 2013 ; Tikka et al, 2013 , 2014 , 2015 ). These parallel observations with alpha and gamma spectral frequencies contrast with the response of delta-theta and beta activities to NMDA receptor blockade as the reduction in current density with ketamine, particularly in the low frequencies, is contrary to the observation that increased local and global EEG delta/theta is one of the more consistent findings reported in unmedicated, first episode, and chronic SZ patients ( Boutros et al, 2008 ; Moran and Hong, 2011 ; Kim et al, 2015 ).…”
Section: Discussionsupporting
confidence: 79%
“…As with delta/theta findings ( Galderisi et al, 2009 ), these inconsistencies can be partially attributed to the effects of chronicity, medication and patient symptomatology ( Czobor and Volovka, 1992 ; Merlo et al, 1998 ; Knott et al, 2001 ; Cerdán et al, 2005 ; Venables et al, 2009 ; Moran and Hong, 2011 ). The recent interest in resting gamma activity, increased in some ( Czobor and Volovka, 1992 ; Merlo et al, 1998 ; Knott et al, 2001 ; Cerdán et al, 2005 ; Kam et al, 2013 ; Kocsis et al, 2013 ; Tikka et al, 2013 , 2014 , 2015 ) but not all EEG or MEG studies ( Sponheim et al, 1994 ) of SZ patients ( Rutter et al, 2009 ; Fuggetta et al, 2014 ; Hirano et al, 2015 ) is of particular interest both because of its purported role in feature binding and coordination of local neuronal populations, and because these rhythms are in part dependent on the activity of Parvalbumin-containing GABAergic cortical inhibitory interneurons, which are diminished in SZ patients and subject to NMDAR modulation from excitatory pyramidal cells ( Lee et al, 2003 ; Herrmann and Dermirlap, 2005 ; Sun et al, 2011 ; Gandal et al, 2012 ; Lewis et al, 2012 ; Cohen et al, 2015 ). Integrative brain functions, however, are modulated through multiple oscillatory processes in different frequency bands, each with differing neuropharmacological sensitivities.…”
Section: Introductionmentioning
confidence: 99%
“…found no group differences with 'eyes closed', but increased spontaneous power in familial high risk subjects with 'eyes open'. In terms of coherence,Bandyopadhyaya, Nizamie et al (2011) reported decreased spectral coherence at rest, whileTikka, Nizamie et al (2015) found no differences in inter or intra hemispheric spectral coherence.…”
mentioning
confidence: 77%
“…one using both groups Tikka, Nizamie et al (2015). reported a negative correlation between low gamma power (30-50Hz) in the left temporal region and Positive and Negative Syndrome Scale (PANSS) general psychopathology subscale (r=0.427 p<0.05); a positive correlation between high gamma power (70-100Hz) in the right occipital region and the PANSS general psychopathology subscale; and a negative correlation between PANSS total scores and left temporal gamma power at both 30-50Hz (r=0.473 p<0.01) and at 50-70Hz (r=0.389 p<0.05) Taylor, McCarley et al (2013).…”
mentioning
confidence: 99%
“…These findings are crucial as very few studies till date have focussed on resting state EEG gamma band oscillations in SZ. 16,43 Earlier studies on dense array EEG have found resting state gamma band abnormalities (increased gamma spectral power) over the left temporal region, parietal and central regions, 44 which are suggested as trait markers of SZ. Indeed, high gamma-band oscillations may be a sensitive marker of impaired neural oscillations in SZ, which is in the range and above of effect sizes for event-related potentials.…”
Section: Social Anhedonia Temporal Experience Of Pleasure and Schizomentioning
confidence: 99%